2005
DOI: 10.1038/sj.bjc.6602800
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of 5-fluorouracil as adjuvant systemic chemotherapy in colorectal cancer: the IGCS-COL multicentre, randomised, phase III study

Abstract: The aims of this multicentre, randomised phase III trial were to evaluate: (1) the role of levamisol (LEV); and (2) the role of folinic acid (FA), added to 5-fluorouracil (5FU) in the adjuvant treatment of colorectal cancer. Patients with histologically proven, radically resected stage II or III colon or rectal cancer were eligible. The study had a 2 Â 2 factorial design with four treatment arms: . Nonhaematological toxicity (all grade vomiting, diarrhoea, mucositis, congiuntivitis, skin, fever and fatigue) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 25 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…21 Previous studies have demonstrated greater adverse events such as mucositis, fever, vomiting, and diarrhea with higher doses of leucovorin. 12,22 Overall, in our highly select population, both leucovorin dosing strategies were well tolerated.…”
Section: Discussionmentioning
confidence: 98%
“…21 Previous studies have demonstrated greater adverse events such as mucositis, fever, vomiting, and diarrhea with higher doses of leucovorin. 12,22 Overall, in our highly select population, both leucovorin dosing strategies were well tolerated.…”
Section: Discussionmentioning
confidence: 98%